China's Domestic and International Migration Development - Wang, Huiyao; Miao, Lu (International Talent Development in China, 2019)
This book offers the most comprehensive, up-to-date assessment of China's domestic and international migration. Restructuring economic development requires large numbers of educated and skilled talents, but this effort comes at a time when the size of China's domestic workforce is shrinking. In response, both national and regional governments in China have been keen to encourage overseas Chinese talents and professionals to return to the country. Meanwhile, the Chinese government has initiated a number of policies to attract international highly-skilled talents and enhance the country's competitiveness, and some Chinese policies have started attracting foreign talents, who are coming to the country to work, and even to stay. Since Chinese policies, mechanisms, and administration efforts to attract and retain skilled domestic or overseas talents are helping to reshape China's economy and are significantly affecting the cooperation on migration and talent mobility, these aspects, in addition to being of scholarly and research interest, hold considerable commercial potential.